Preparing for Future Forest Fires: Emerging Technologies and Innovations - Ahmad Ainuddin Nuruddin (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Forest fires are part of the global ecosystems occurring for a long time in earth history. These forest fires are part of the processes which establish the ecosystems and directly influence plant species composition within the ecosystems. However, the anthropogenic effect has changed this relationship causing an increasing number of forest fires Human activities have also changed world climate and future climate is expected to increase in temperature with dire consequences on the earth environment. These changes will profoundly impact on the earth’s socio-economic and human well-being. One of the effects of higher global temperature is increasing forest fires occurrences with stronger intensities. There is a need to develop innovation and new technologies to manage these future fires. This paper aims to review various innovations and new technologies that can be used for the whole spectrum of forest fire management, from forest fire prediction to forest restoration of burnt areas. Emerging technologies such as geospatial technologies, the Internet of Things (IoT), Artificial Intelligence, 5G & enhanced connectivity, the Internet of Behaviors (IoB), virtual and augmented reality, and robotics are discussed and potential applications to forest fire management are discussed. Adaptation of these technologies is vital in the effective management of future forest fires. Key words: Climate Change, Future Fires, Innovations